Terrariums approach in cafe design on people’s eating behaviour - Aisya Nadra Binti Ahmad Nizam; Roslan Talib (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Nature-inspired cafés have become a trend in modern interior design, promoting quality health and well-being for the customers. To encourage people to bring nature into the built environment, terrariums have taken up the interior space to improve the quality of life. Terrariums are one of the preferred indoor gardening options that only require an individual's creativity, with or without professional knowledge. However, the terrariums approach to interior spaces is still uncommon in Malaysia, and how the terrarium approach enhances people’s eating behaviour remains unexplored. With the emerging trend of Mossarium KL, the concept of terrariums is used as part of the interior design as well as positive factors that enhance people’s eating behaviour. This paper aims to study the terrariums approach in built environments and to review the enhancements of the terrarium on people’s eating behaviour. A case study had been done on the Mossarium KL in Petaling Jaya, Selangor that adapted the concept of a terrarium in the interior space. This study's conceptual framework is based on the idea of employing terrariums as an interior landscape for exploring their potential impact on individual eating habits. This study highlights the importance of incorporating nature-based interventions, such as terrarium cafes within interior spaces and providing valuable insights into people’s eating behaviours in the cafes.